Strategi, Tantangan, Regulasi dan Migrasi Rekam Medis Elektronik di RST dr. Soedjono Magelang - Praptana; Kuswanto Hardjo; Laili Rahmatul Ilmi (Universitas Jenderal Achmad Yani Yogyakarta, 2021)
Medical records can be maintained both manually and electronically, the transition process from manual and electronic medical records is certainly not easy because it must have a strategy and readiness, both from facilities and infrastructure. Of course, using electronic medical records is still obliged to pay attention to legal aspects that cover not only for the sake of achieving patient safety but also for health service providers. Socialization is needed that discusses overarching regulations, strategies, and challenges that must be faced and prepared in the process of change. So that the migration process from manual to electronic can be carried out well according to the expectations of users and policymakers.